Analisis Kesulitan Belajar Mahasiswa dalam Mempelajari Teorema Stokes pada Mata Kuliah Kalkulus Vektor - Septiani Agustina Siregar; Alivia Ivo Amirah Ghania Nasution; Eka Elsiani Tanjung; Suci Dahlya Narpila (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to analyze students' learning difficulties in understanding Stokes' Theorem in the Vector Calculus course. The method used is descriptive qualitative with data collection techniques through interviews with students who have taken the Vector Calculus course. The results of the study indicate that students have difficulty in understanding the relationship between line and surface integrals, determining the normal orientation of the surface according to the right-hand rule, and performing proper surface parameterization. In addition, the complexity of calculating the rotation of the vector field is also a challenge. Students suggest the use of interactive visual media and gradual exercises as effective strategies in facilitating understanding of the concept. This study provides important recommendations for lecturers and curriculum developers to improve the quality of Vector Calculus learning through a more applicable and visual approach.